2011
DOI: 10.2341/10-218l
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Temperature: Effects on Adhesive Properties and Resin-Dentin Bond Strength

Abstract: AD Loguercio D Salvalaggio AE Piva CA Klein-Jú nior M de LR Accorinte MM Meier RHM Grande A Reis Clinical RelevancePreheating ethanol/water-based adhesive systems could be useful to improve the hybrid layer quality. SUMMARYObjectives: To evaluate the effect of adhesive temperature on the resin-dentin bond strength (lTBS), nanoleakage (NL), adhesive layer thickness (AL), and degree of conversion (DC) of ethanol/water-(SB) and acetone-based (PB) etch-and-rinse adhesive systems.Methods: The bottles of the two adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
4
14
1
1
Order By: Relevance
“…In this study, the DC values found for the two control groups (PB and OS) were in agreement with values in the literature (21,23). Leitune et al (2) found no difference in the DC when incorporating Nb 2 O micro-filler into an experimental adhesive system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the DC values found for the two control groups (PB and OS) were in agreement with values in the literature (21,23). Leitune et al (2) found no difference in the DC when incorporating Nb 2 O micro-filler into an experimental adhesive system.…”
Section: Discussionsupporting
confidence: 92%
“…The dentin surface was etched with 37% H 3 PO 4 (15 s), rinsed for 15 s, and kept the dentin slightly moist, so that all adhesives were applied on the moist substrate (21); two layers of the adhesive system were applied, and soft air jets were blown on the samples for 10 s, followed by polymerization (Optilux 501, Kerr, Orange, CA, USA) at 600 mW/cm² for 20 s. Table 1 shows the application mode, composition, manufacturer and lot number of the used materials. After the adhesive procedure, a 6.0 mm high composite resin restoration (Lis, FGM, Joinville, SC, Brazil) was performed in three 2-mm increments of and light polymerized for 40 s.…”
Section: Microtensile Bond Strengthmentioning
confidence: 99%
“…Some studies have shown that temperature has an effect on the properties and bond strength of the adhesives, (13)(14)(15) whereas other studies have reported that the temperature of the adhesive before it is used does not significantly affect the bond strength (16) In the former studies, the lowest SBS values were reported in restorations made with adhesives used immediately they were removed from a refrigerator (at 4°C). The viscosity of an adhesive is high at low temperatures, and its increase prevents proper wetting of the substrate due to a low spreading velocity of the adhesive (17) Another reported consequence of refrigerating polymer-based materials is that it may reduce the vapor pressure of the solvents present, thus inhibiting their evaporation from the adhesive layer (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the solvents and the water present in the adhesive should ideally be removed to a sufficient degree because residual solvents can inhibit the polymerization and negatively affect the mechanical properties of the adhesive 16 , 26 . Hence, a clinical approach to improve the adhesive properties indicates the use of warm air 9 , 13 , 16 , 19 , 20 , 26 to facilitate the evaporation of the solvent as well as the use of preheated adhesive systems 11 , 18 , 25 , 28 in order to increase the speed of permeation of the monomers and the evaporation of the residual monomeric content. The quality and the stability of the hybrid layer can be influenced by the heating of adhesive through the stimulation of their chemical reactions and, thus, some properties of the monomeric solutions, such as degree of monomer conversion and viscosity, can be changed by temperature 1 , 11 , 18 , 23 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a clinical approach to improve the adhesive properties indicates the use of warm air 9 , 13 , 16 , 19 , 20 , 26 to facilitate the evaporation of the solvent as well as the use of preheated adhesive systems 11 , 18 , 25 , 28 in order to increase the speed of permeation of the monomers and the evaporation of the residual monomeric content. The quality and the stability of the hybrid layer can be influenced by the heating of adhesive through the stimulation of their chemical reactions and, thus, some properties of the monomeric solutions, such as degree of monomer conversion and viscosity, can be changed by temperature 1 , 11 , 18 , 23 , 28 . Temperature can increase the mobility of free radicals, benefiting the polymerization of the adhesive by increasing the degree of conversion 1 , besides decreasing the viscosity and improving the speed of spreading of the adhesive and deeper penetration into dentin 11 , 18 , 25 , 28 .…”
Section: Introductionmentioning
confidence: 99%